Biblioterapija v knjižnici - Zabukovec, Vlasta (Knjižnica, 2017)
Bibliotherapy is a counselling process on books or with books. It is a nondirective counselling method with important influence on reader's emotional, cognitive and social aspect. Starting points of bibliotherapy and bibliocounselling will be presented. 48 librarians included into the research confirmed that they had already some experience with bibliotherapy, but on the other side the systematic training for developing appropriate competences is needed. On the basis of this conclusion and according to the theoretical framework, it is suggested to use the term "bibliocounselling" instead of "bibliotherapy".
Keywords: bibliocounselling; bibliosvetovanje; bibliotekarji; biblioterapija; bibliotherapy; competences; knjižnice; kompetence; librarians; users